2000
DOI: 10.1038/sj.leu.2401612
|View full text |Cite
|
Sign up to set email alerts
|

Simple methods for the rapid exchange of flow cytometric data between remote centers

Abstract: CORRESPONDENCESimple methods for the rapid exchange of flow cytometric data between remote centers TO THE EDITORThe flow cytometric analysis of cellular immunophenotypes and DNA content has become indispensable in the modern classification of leukemia and lymphoma. The multiple applications of this technology include determination of the lineage association of malignant cells, assessment of their clonality, identification of prognostic indicators and monitoring of minimal residual disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Continued training of study group members was pursued to support the standardization process, i.e., (i) Rotational personnel exchange (multiple day site visits), (ii) Twice-yearly entire group workshops with written summary reports, (iii) Joint list-mode data (LMD) file reviewing during workshops or online via FTP-server (access limited to group members) (21). LMD files could be exchanged between BC and BD software and , but these can undoubtedly be added to the leukemic cluster.…”
Section: Materials and Methods Standardized Flow Cytometrymentioning
confidence: 99%
“…Continued training of study group members was pursued to support the standardization process, i.e., (i) Rotational personnel exchange (multiple day site visits), (ii) Twice-yearly entire group workshops with written summary reports, (iii) Joint list-mode data (LMD) file reviewing during workshops or online via FTP-server (access limited to group members) (21). LMD files could be exchanged between BC and BD software and , but these can undoubtedly be added to the leukemic cluster.…”
Section: Materials and Methods Standardized Flow Cytometrymentioning
confidence: 99%
“…Finally, the simultaneous analysis of several parameters can also help to determine with greater accuracy the presence of functionally important cell subsets, such as those with "stem cell" features (32). These advantages notwithstanding, several studies demonstrated that MRD monitored by four-color FCM can still be clinically informative (11,37,38).PFC may introduce the potential for technical problems. For example, setting up multicolor FCM for MRD analysis is not simply achieved by adding new reagents to existing panels but requires careful testing, validation, and quality control (26,39,40).…”
mentioning
confidence: 99%
“…Web-based consultation with SJCRH, as described previously, facilitated quality control. 10 A total of 1148 diagnostic specimens (1089 bone marrow, 59 blood) from 1118 patients were analyzed. Of these, 30 were recollected to replace specimens that could not be evaluated because of nonviable cells due to delayed shipping or processing (n ¼ 11), bacterial contamination (n ¼ 3), dilution of bone marrow with blood (n ¼ 6), or inconclusive findings (n ¼ 10).…”
mentioning
confidence: 99%
“…Ongoing training and quality assurance were accomplished by our innovative use of a webbased system for rapid exchange of flow cytometric data between centers, which proved highly effective. 10 Importantly, in the fifth year of the program, after analysis of hundreds of cases, the reference laboratory rarely required consultation with SJCRH (3% of cases) and the consultations refined or altered the diagnosis in only 1% of all cases (two of eight consulted cases). We consider this program to be a paradigm of technology transfer from developed countries to those with limited resources in a way that builds local capacity and fosters independence -characteristics essential for sustainable development.…”
mentioning
confidence: 99%